Phân tích phát sinh với việc xác lập quy tắc âm vị học về dấu hiệu số nhiều trong danh từ tiếng Anh - Võ, Đại Quang (H. : ĐHQGHN, 2017)
(i) Derivational analysis as an approach in the establishment of phonological rules; (ii) Information about how underlying representations are to be made explicit; (iii) The two phonological rules established in terms of derivational analysis: a. i-epenthesis; b. voicing assimilation; (iv) Problems intended to be discussed in other articles.